Beispiel Nr: 14
$ \text{Gegeben:} \\ a1 \cdot x +b1 \cdot y =c1\\ a2 \cdot x +b2 \cdot y =c2 \\ \\ \text{Gesucht:} \\\text{x und y} \\ \\ \textbf{Gegeben:} \\ \\ 2 x +3 y =4\\ \frac{1}{3} x -\frac{1}{5} y = 12 \\ \\ \\ \\ \textbf{Rechnung:} \\\begin{array}{l|l} \begin{array}{l} I \qquad 2 x +3 y =4\\ II \qquad \frac{1}{3} x -\frac{1}{5} y = 12 \\ \text{I nach y auflösen}\\ 2 x +3 y =4 \\ 2 x +3 y =4 \qquad /-2 x\\ 3 y =4 -2 x \qquad /:3 \\ y =1\frac{1}{3} -\frac{2}{3} x \\ \text{II nach y auflösen}\\ \frac{1}{3} x -\frac{1}{5} y =12 \\ \frac{1}{3} x -\frac{1}{5} y =12 \qquad /-\frac{1}{3} x\\ -\frac{1}{5} y =12 -\frac{1}{3} x \qquad /:\left(-\frac{1}{5}\right) \\ y =-60 +1\frac{2}{3} x \\ \text{I = II}\\ 1\frac{1}{3} -\frac{2}{3} x =-60 +1\frac{2}{3} x \qquad /+\frac{2}{3} x /+60 \\ 1\frac{1}{3}+60 =1\frac{2}{3} x +\frac{2}{3} x \\ 61\frac{1}{3} =2\frac{1}{3} x \qquad /:2\frac{1}{3} \\ x=26\frac{2}{7} \\ \text{x in I}\\ y =1\frac{1}{3} -\frac{2}{3} \cdot 26\frac{2}{7} \\ y=-16\frac{4}{21} \\ L=\{26\frac{2}{7}/-16\frac{4}{21}\} \end{array} & \begin{array}{l} I \qquad 2 x +3 y =4\\ II \qquad \frac{1}{3} x -\frac{1}{5} y = 12 \\ \text{I nach x auflösen}\\ 2 x +3 y =4 \\ 2 x +3 y =4 \qquad /-3 y\\ 2 x =4 -3 y \qquad /:2 \\ x =2 -1\frac{1}{2} y \\ \text{II nach x auflösen}\\ \frac{1}{3} x -\frac{1}{5} y =12 \\ \frac{1}{3} x -\frac{1}{5} y =12 \qquad /+\frac{1}{5} y\\ \frac{1}{3} x =12 +\frac{1}{5} y \qquad /:\frac{1}{3} \\ x =36 +\frac{3}{5} y \\ \text{I = II}\\ 2 -1\frac{1}{2} y =36 +\frac{3}{5} y \qquad /+1\frac{1}{2} y /-36 \\ 2-36 =\frac{3}{5} y +1\frac{1}{2} y \\ -34 =2\frac{1}{10} y \qquad /:2\frac{1}{10} \\ y=-16\frac{4}{21} \\ \text{y in I}\\ x =2 -1\frac{1}{2} \cdot -16\frac{4}{21} \\ x=26\frac{2}{7} \\ L=\{26\frac{2}{7}/-16\frac{4}{21}\} \end{array} \end{array} $